Implementation of Universal Dynamic Bandwidth Allocation Algorithm in Smart Grid Environment - Ridwan M.A.; Radzi N.A.M.; Abdullah F.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power transmission networks; Frequency allocation; Grid computing; Photonics; Quality of service; Queueing theory; Smart power grids; Available bandwidth; Bandwidth management; Dynamic bandwidth allocation; Dynamic bandwidth allocation algorithms; Excess bandwidths; LabViEW; Priority queues; Smart grid; Bandwidth